2010
DOI: 10.1002/yea.1812
|View full text |Cite
|
Sign up to set email alerts
|

Differences in hydrolytic abilities of two crude lipases from Geotrichum candidum 4013

Abstract: The fungus Geotrichum candidum 4013 produces two types of lipases (extracellular and cell-bound). Both enzymes were tested for their hydrolytic ability to pnitrophenyl esters and compounds having a structure similar to the original substrate (triacylglycerols). Higher lipolytic activity of extracellular lipase was observed when triacylglycerols of medium-(C12) and long-(C18) chain fatty acids were used as substrates. Cell-bound lipase preferentially hydrolysed trimyristate (C14). The differences in the abiliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 39 publications
(48 reference statements)
0
20
0
2
Order By: Relevance
“…The concentrations used vary greatly, but the range from 0.1 to 5.0 % w/w is more commonly used, and organic sources are added in higher quantities than inorganic sources . Concentrations (% w/w) of: 5.0 of peptone; 2.0 of yeast extract and 0.1 of NaNO 3 and 0.5 of NH 4 NO 3 are commonly applied in the lipase production [43][44][45][46]49,57 ; however, optimized studies about medium composition reduced or eliminated some nitrogen sources in the process. Burket et al and Maldonado et al showed that 3.58 % w/w of peptone is enough to obtain a high level of lipase activity from G. candidum.…”
Section: Production Of Geotrichum Spp Lipasesmentioning
confidence: 99%
See 4 more Smart Citations
“…The concentrations used vary greatly, but the range from 0.1 to 5.0 % w/w is more commonly used, and organic sources are added in higher quantities than inorganic sources . Concentrations (% w/w) of: 5.0 of peptone; 2.0 of yeast extract and 0.1 of NaNO 3 and 0.5 of NH 4 NO 3 are commonly applied in the lipase production [43][44][45][46]49,57 ; however, optimized studies about medium composition reduced or eliminated some nitrogen sources in the process. Burket et al and Maldonado et al showed that 3.58 % w/w of peptone is enough to obtain a high level of lipase activity from G. candidum.…”
Section: Production Of Geotrichum Spp Lipasesmentioning
confidence: 99%
“…Some examples are babassu, cottonseed, fish, olive, soybean oils; almond, coconut, ginger, groundnut Jatropha, niger seed oil cakes, palm and sunflower effluents, and many others . Olive oil contains a high concentration of C18:1 unsaturated fatty acid, and innumerous studies indicate the use of this oil as an inductor for lipase production 44,45,[47][48][49]51,57,56 . Soybean oil also shows similar results due to its similar composition to olive oil, and its low cost is a strong appeal for its application.…”
Section: Production Of Geotrichum Spp Lipasesmentioning
confidence: 99%
See 3 more Smart Citations